Allogeneic stem-cell transplantation in HIV-1-infected patients with high-risk hematological disorders - Kwon, Mi; Bailén, Rebeca; Balsalobre, Pascual; Jurado, Manuel; Bermudez, Arancha; Badiola, Jon; Esquirol, Albert; Miralles, Pilar; López-Fernández, Elisa; Sanz, Jaime; Yañez, Lucrecia; Colorado, Mercedes; et al. (AIDS (London), 2019)
INTRODUCTION:Although a number of patients with HIV infection and hematological disease have successfully undergone allogeneic hematopoietic stem-cell transplantation (HSCT), short and long-term outcomes remain not well known. We report the largest Spanish experience treating HIV-infected adult patients with high-risk hematological malignancies with allogeneic HSCT. METHODS:We retrospectively reviewed 22 HIV-positive patients who received allogeneic HSCT in five centers in Spain. RESULTS:A total of 22 patients with high-risk hematological malignancies were transplanted between 1999 and 2018. Median age was 44 years. With a median follow-up of 65 months (8–112), overall survival and event-free survival were 46%. Nonrelapse mortality was 14% at 12 months and relapse was 24% at 24 months. Grade II–IV acute graft-versus-host disease (GVHD) rate was 44%, and moderate/severe chronic GVHD rate was 41% at 24 months. All patients received combination antiretroviral therapy. Two patients showed severe toxicity related to drug interaction with antiretroviral therapy. 68% of patients showed infectious complications with viral infections as the most frequent cause. Two patients had invasive aspergillosis and one patient presented disseminated tuberculosis. All survivors except one maintained undetectable HIV load at last follow-up after HSCT. CONCLUSION:Allogeneic HSCT is an effective therapy for high-risk hematological malignancies in patients with HIV infection, and long-term HIV suppression with combination antiretroviral therapy is feasible. However, drug interactions with antiretroviral agents, occurrence of GVHD, and frequent infectious complications account for a complex procedure in this population. Selected HIV-infected patients with hematologic malignancies should be considered for allo-HSCT when indicated, in experienced centers.